Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1016/j.ydbio.2007.10.018
|View full text |Cite
|
Sign up to set email alerts
|

A nutritional model of late embryonic vitamin A deficiency produces defects in organogenesis at a high penetrance and reveals new roles for the vitamin in skeletal development

Abstract: Vitamin A plays an essential role in vertebrate embryogenesis. In the present study, pregnant vitamin A-deficient (VAD) rats were maintained during early pregnancy on the short half-life vitamin A metabolite, all-trans retinoic acid (atRA), in an amount sufficient to support normal development to E10.5, with a higher level of atRA (250 microg atRA/g diet) provided from embryonic day (E) 8.5-10.5 to prevent mid-gestational resorption. When limiting amounts of atRA (1.5 or 12 microg/g diet) were provided after E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
74
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 57 publications
9
74
1
Order By: Relevance
“…Our findings support the hypothesis that maternal VAD could induce vertebral anomalies in the offspring. Our study has also observed other skeletal abnormalities include loss of the neural arch of cervical vertebrae 1, malformation of sternum, loss of the ribs, rib fusion, abnormal of forelimb and hindlimb, malformation of the pelvic regions, which have also been observed by others [24,30]. Another important finding of our study is that VAD repressed the expression RALDHs and RARs, which are important components of RA signaling, in the liver and vertebral body of VAD rats.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings support the hypothesis that maternal VAD could induce vertebral anomalies in the offspring. Our study has also observed other skeletal abnormalities include loss of the neural arch of cervical vertebrae 1, malformation of sternum, loss of the ribs, rib fusion, abnormal of forelimb and hindlimb, malformation of the pelvic regions, which have also been observed by others [24,30]. Another important finding of our study is that VAD repressed the expression RALDHs and RARs, which are important components of RA signaling, in the liver and vertebral body of VAD rats.…”
Section: Discussionsupporting
confidence: 88%
“…It was later discovered that dietary supplementation of VAD rats with either vitamin A or RA overcame the block in meiosis and restored male fertility (Morales and Griswold 1987;Van Pelt and De Rooij 1990). Studies of female VAD rats determined that 40 -230 mcg/rat/day of RA was required for ovulation, fertilisation, implantation and subsequent embryo development: the higher doses needed from mid-gestation onwards (Kaiser et al, 2003;See et al, 2008;White et al, 2000b;White et al, 1998). Such studies have uncovered the important roles for RA during many aspects of development, reviewed by (Clagett-Dame and Knutson 2011).…”
Section: Is Retinoic Acid Necessary For Meiosis?mentioning
confidence: 99%
“…34 A rat study found that inducing VA deficiency in late pregnancy resulted in less growth of intestinal villi in the small intestine of fetuses. 35 The difference in liver retinol storage between LBW and HBW piglets may be due to length of the absorptive intestinal tract or stellate cell development. Little is known about the specific development of stellate cells, other than that their production arises from mesenchymal stem cells.…”
Section: Discussionmentioning
confidence: 99%